Interaction with AEG-1 and MDM2 is associated with glioma development and progression and correlates with poor prognosis. Issue 2 (17th January 2019) - Ding, Zongmei; Zhang, Zilan; Jin, Xu; Chen, Pin; Lv, Fang; Liu, Dan; Shen, Yating; Li, Yan; Gu, Xuewen
ABSTRACT: Glioma is the most common central nervous system tumor with poor prognosis. The AEG-1 (Astrocyte Elevated Gene 1) gene displays oncogenic characteristics, including proliferation, metastasis, chemoresistance, invasion, and evasion of apoptosis, and is strongly linked to the occurrence of glioma. Here, we elucidated the potential contribution of AEG-1 in human glioma pathogenesis. In glioma cells, AEG-1 could directly interact with Murine Double Minute-2 (MDM2) protein resulting in MDM2-p53-mediated cell proliferation and apoptosis. MDM2 is being revealed as an oncoprotein, which is involved in many human cancers progression. By immunohistochemical and a multivariate analysis, expressions of AEG-1 and MDM2 were elevated in glioma and high AEG-1 and MDM2 expressions were showed to be correlated with poor prognosis. AEG-1-MDM2 interaction prolonged stabilization of MDM2 where AEG-1 inhibited ubiquitination and subsequent proteasome-mediated degradation of MDM2 protein. Moreover, slicing AEG-1 blocked MDM2 expression and then impacted MDM2-p53 pathway that influenced cell proliferation and apoptosis. These findings uncover a novel AEG-1-MDM2 interplay by which AEG-1 augments glioma progression and reveal a viable potential therapy for the treatment of glioma patients.